CRITICAL PREPAREDNESS, READINESS AND RESPONSE TO COVID-19 PANDEMIC: A NARRATIVE REVIEW - Ravindra Pathirathna; Pamila Adikari; Dedunu Dias; Udara Gunathilake (Universitas Airlangga, 2020)
Background: The COVID-19 was declared as a pandemic by the World Health Organization (WHO). Globally, countries took actions to slow the spread and avoid overwhelming the health system. The WHO issued interim guidelines on critical preparedness, readiness and response actions against COVID-19 to assist level of preparedness and readiness.Aim: This study reviewed the work of Australia, Singapore, Sri Lanka and the United Kingdom on actions and priority areas of work as described in interim guidelines by the WHO in relation to the first two phases of disease transmission scenario.Methods: A non-systematic narrative review was conducted. Relevant documents available in selected websites were searched. The data generated were compiled, and information was synthesised within the WHO framework for critical preparedness, readiness and response actions against COVID-19. Further, scenarios of